2018
DOI: 10.7150/thno.22958
|View full text |Cite
|
Sign up to set email alerts
|

Exosomal DMBT1 from human urine-derived stem cells facilitates diabetic wound repair by promoting angiogenesis

Abstract: Chronic non-healing wounds represent one of the most common complications of diabetes and need advanced treatment strategies. Exosomes are key mediators of cell paracrine action and can be directly utilized as therapeutic agents for tissue repair and regeneration. Here, we explored the effects of exosomes from human urine-derived stem cells (USC-Exos) on diabetic wound healing and the underlying mechanism.Methods: USCs were characterized by flow cytometry and multipotent differentiation potential analyses. USC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
268
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 286 publications
(293 citation statements)
references
References 51 publications
(68 reference statements)
10
268
0
Order By: Relevance
“…By exchange of material such as RNAs, miRNAs, proteins and delivering information, exosomes have been viewed as important mediators of cell‐cell communication . Recipient cells can recycle exosomes back to the extracellular milieu after being taken up by endocytosis . A recent study indicated the paracrine effects of endothelial exosomes .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…By exchange of material such as RNAs, miRNAs, proteins and delivering information, exosomes have been viewed as important mediators of cell‐cell communication . Recipient cells can recycle exosomes back to the extracellular milieu after being taken up by endocytosis . A recent study indicated the paracrine effects of endothelial exosomes .…”
Section: Discussionmentioning
confidence: 99%
“…46 Recipient cells can recycle exosomes back to the extracellular milieu after being taken up by endocytosis. 47,48 A recent study indicated the paracrine effects of endothelial exosomes. 24 In this study, the exosomes were identified using morphology, size and exosomal markers.…”
Section: Discussionmentioning
confidence: 99%
“…In a mouse model of a skin defect, Fang et al found that hucMSC-EXs contain miR-21, miR-23a, miR-125b, and miR-145, which could synthetically antagonize the TGF-β/Smad2 signaling pathway and inhibit the differentiation and accumulation of myofibroblasts, thus reducing scar formation and promoting wound healing [52]. In another study, Chen et al demonstrated that USC-EXs showed a favorable therapeutic effect on diabetic skin ulcers through that was deleted in malignant brain tumors 1 (DMBT1) [53].…”
Section: Skinmentioning
confidence: 99%
“…The endocytic pathway involves the formation of endosomes via a fundamental pathway for the entrance into the cell of large cargoes; the biogenesis of intraluminal vesicles, which are precursors of Exos, in endosomes for the transformation from early endosomes to MVBs, and the fusion between cytomembrane and MVB membrane to release Exos to the outside of the cell. Although initially dismissed as artefacts or “cell debris”, it is now clear that these nano-sized vesicles act as “correspondents” in intercellular communication [18,20,21]. EVs tend to express similar membrane proteins to their parent cells, which could give them potential targeting ability, and, in addition, could make them potential detection targets for use in liquid biopsy.…”
Section: Extracellular Vesiclesmentioning
confidence: 99%